Oltre il muro dell’intolleranza. Luci e ombre della benedizione nella scuola tra libertà religiosa e laicità dello Stato (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: - 1. La libertà religiosa: brevi cenni - 2. Libertà di coscienza e libera formazione delle coscienze - 3. Istanze identitarie, libertà religiosa e principio di uguaglianza - 4. Fattore religioso e semantiche radici della laicità dello Stato - 5. Attività religiose e pratiche di culto nella scuola pubblica: il quadro normativo - 6. Il rito di benedizione nella scuola pubblica: revirement giurisprudenziale - 7. La recente sentenza del Consiglio di Stato, 27 marzo 2017, n. 1388 - 8. Atti di culto nello spazio pubblico e finalità formativa della scuola - 9. Conclusioni.Breaking through the wall of intolerance. Lights and shadows of Easter blessing in State schools between religious freedom and laical nature of the StateABSTRACT: Religious freedom is a fundamental human right protected by Italian Constitution. Which are the limits to be respected in case of religious practices inside Italian State schools? This paper examines the meaning of “religious freedom” and the essence of State “secular” nature; then focuses on a recent case, which caused a debate on the boundaries between Church and State, about Easter blessing rite in State schools. The Court of first instance argued that blessing is a religious rite and it cannot be held in State schools; the Supreme Administrative Court rejected this ruling, claiming that Easter blessing in State schools is to be permitted, it being an exercise of religious freedom not violating State secular nature. Religious symbols and rites in public places are not to be considered a violation of the State secular nature. The Italian State does not hold any religious belief of any religion, but can create conditions conducive to religions.